Staging in the Cultural and Educational Activities of a Museum - Spesivtseva Nadezhda; Mamontova Marina; Viaznikova Victoria (Communications of International Proceedings, 2020)
The article examines the problem of integration of theatrical and museum techniques in the museum space, reveals the directions of staging in museums, gives examples of staging in the cultural and educational activities of museums.
Keywords: Museum; Staging; Theater in A Museum; Cultural and Educational Activities of A Museum.